Neolithic cultural sites and extreme climate related channel avulsion: Evidence from the Vaigai River Basin, southern India - Ramkumar, M. (Elsevier Ltd, 2021)
We document evidence for the role of fluvial dynamics-stream channel avulsion and flooding, tectonics and climatic conditions on the occurrence, shifting and burial of ancient cultural sites in the Vaigai River Basin in southern India. Systematic regional mapping, geophysical investigations and archaeological excavations in the flood plains of the Vaigai River led to the unearthing of an ancient culture that thrived at least since 752 BCE (2435 Â± 34 BP). Evidence for early human activities include sites of ancient and now buried industries that were manufacturing steel, glass bead, dye, gold jewelry and earthenware, in addition to dwelling-habitation, sites of religious sacrificial ceremonies, and places of worship, and burial. These information together with the occurrences of microlithic age stone tools in the vicinity led to the proposition of continued habitation of the Vaigai River Basin until today. Radiometric dating shows oldest age of 2435 Â± 34 BP (752 BCE) obtained at 2.5 m depth in a pit excavated at Keezhadi, a location situated far from the present day channel course whereas the youngest age of 689 Â± 24 BP is obtained at Agaram, a location situated nearest to the present day channel course. The bone fragments were dated as 1115 Â± 39 BP (778 CE â 1016 CE) and 1229 Â± 30 BP (689 CE â 883 CE). The organic carbon/peat layers recovered between flood deposits at the upper reaches of the Vaigai River are dated as 830 Â± 30 BP and 1250 Â± 30 BP. The natural levee deposits show evidences of habitation-related disturbances in the internal sedimentary structure, texture and packing. In addition to occurrences of hearth etc., recurrences of overbank-channel deposits over natural levee-habitation surfaces indicate habitation-colonization over relatively highgrounds along river bank, followed by marooning/burial under overbank-channel deposit and abandonment of habitation site and/or shifting of habitat. The same sequence of events occurred again, showing two habitation surfaces that are buried under surface currently. Together with facies characteristics and other artifact occurrences, the ages obtained in our study indicate shifting of the Vaigai River from prior to 2435 BP and colonization of ancient population, which might have been affected by a catastrophic flood and stream avulsion at about 1250â830 BP. These resulted in the ancient habitation getting marooned, industries and other structural infrastructure destroyed, and were transported and deposited as interbeds in flood deposits. Following a reduction in the stream energy, the point bar-natural levee environmental setting paved way for the deposition of organic carbon layer at Agaram at about 690 BP. This was followed by lateral shifting of the channel from Agaram towards the present-day course. Â© 2021 Elsevier Ltd